2018
DOI: 10.1161/jaha.117.007231
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions Following a Hospitalization for Cardiovascular Events in Dialysis Patients: A Retrospective Cohort Study

Abstract: BackgroundHospitalization for cardiovascular disease (CVD) is common among patients receiving maintenance dialysis, but patterns of readmissions following cardiovascular events are underexplored.Methods and ResultsIn this retrospective analysis of prevalent, Medicare‐eligible patients receiving dialysis in 2012–2013, all live‐discharge hospitalizations attributed to CVD were ascertained. Rates of all‐cause, CVD‐related, and non–CVD‐related readmissions and death in the ensuing 10 and 30 days were calculated. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Moreover, previous studies have demonstrated that CVD is a common cause of readmission in dialysis patients. Indeed, CVD accounted for 40–50% of readmissions in HD patients [ 9 , 10 , 22 ]. Regarding PD, CVD readmission was responsible for nearly 25% of all readmissions within 120 days after dialysis; additionally, 40.8% of these patients tended to have another CVD readmission within the following 30 days [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have demonstrated that CVD is a common cause of readmission in dialysis patients. Indeed, CVD accounted for 40–50% of readmissions in HD patients [ 9 , 10 , 22 ]. Regarding PD, CVD readmission was responsible for nearly 25% of all readmissions within 120 days after dialysis; additionally, 40.8% of these patients tended to have another CVD readmission within the following 30 days [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies investigating the prevalence of readmissions in different dialysis modalities have presented conflicting results. Some studies showed that PD patients were at higher risks of all-cause readmission than HD patients [ 6 ], but some studies yielded a similar readmission rate [ 14 , 22 ]. However, Ross et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the main causes of death in our hemodialysis study population were bloodstream infections by pathogens other than S. aureus (73%), followed by cardiovascular events (14%), and various causes (13%). Previous studies report that the main causes of death are comorbidities that occur alongside with or result from renal insufficiency [24]: cardiovascular events (40%), bloodstream infections (30%) and sudden deaths of patients at home with unknown cause (25%) [29, 30], the latter often again being attributed to cardiovascular events [28]. How S. aureus carriage could influence the overall mortality due to non- S. aureus infections and other, non-infectious diseases remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD), a leading cause of hospitalization and death, is common among patients receiving maintenance dialysis (5,10). Accumulating evidence on dialysis patients suggests that CVD increases the risk of hospital readmission (11)(12)(13)(14). Previous studies on HD patients have suggested that heart failure (HF) increases the risk of hospital readmission (11).…”
Section: Introductionmentioning
confidence: 99%